Analysis of Factors and Obstacles to the Implementation of Multicultural Education in Social Sciences Education in Indonesia - Rosita Anggraeni; Rukhaini Fitri Rahmawati (STKIP Taman Siswa Bima, 2025)
Multicultural education is important to be given to students to prevent conflicts in attitudes of tolerance and social interaction between groups in society. This study aims to find out about the factors that influence the success and obstacles in the implementation of the multicultural education model in social studies learning. This study uses the Systematic Literature Review method. Data collection was carried out based on Google Scholar, with a limitation of 2014-2024. The results of the study indicate that the factors that influence the success of the implementation of the multicultural education model in social studies learning are teacher factors to increase effectiveness in the teaching and learning process, student factors, namely each student has unique characteristics and different ways of thinking, and parent and community factors in the student's environment have an important role in determining the success of children. The obstacles in its implementation are obstacles from teachers who are less competent in teaching, obstacles from students who have different characteristics, and obstacles from parents and the community, namely the diverse external environment.